Development of Web-Based Learning Media on Social Studies Subject at Junior High School Methodist Lubuk Pakam, Indonesia - Emelda Thesalonika; Samsidar Tanjung; Restu Restu; Effendi Manalu (BIRCU, 2019)
Prioritizing WEB-based knowledge learning. The approach taken to familiarize students with high-level thinking is helped by WEB. Based on preliminary analysis, it is known that teachers have difficulties in designing a WEB-based social science learning media. This study uses the ADDIE model to develop web-based learning media. The development research flow, namely, analysis, design, development, implementation, and evaluation. The results of research in the form of WEB-based social studies learning media products have been declared feasible by a team of experts. Practically, this research can be useful for teachers, the government.